Malay reaction to the 1930s economic depression in Malaya - K. Nadaraja (School of History, Politics and Strategic Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The unprecedented World Economic Depression of the 1930s affected Malaya just as it did to numerous other countries in the world. In Malaya’s case, with the rubber and tin industries, the two main pillars of the country’s economy, well integrated with the international market forces, the sudden economic downturn caused the collapse of both these industries, resulting in widespread retrenchment and mass unemployment of workers. To the people of multiracial Malaya the economic meltdown was more than an economic crisis. It was a crisis of all sorts that threatened their very own survival. Despite the colonial government’s efforts to contain the situation every community was displaced in one way or another though by varying degrees. This paper examines some of the immediate effects of the economic depression on the Federated Malay States and confines its discussion to Malay reaction to the crisis – how they were affected, the challenges they faced and how they coped with the crisis and the government’s role in ensuring the protection of the Malays. It also discusses Malay reaction to the presence of immigrant races in the country and their rise to seek greater protection of their rights as natives of the country.